Glycyrrhizin attenuates endotoxin- induced acute liver injury after partial hepatectomy in rats - Tang,B. (2007)
Massive hepatectomy associated with infection induces liver dysfunction, or even multiple organ failure and death. Glycyrrhizin has been shown to exhibit anti-oxidant and anti-inflammatory activities. The aim of the present study was to investigate whether glycyrrhizin could attenuate endotoxin-induced acute liver injury after partial hepatectomy. Male Wistar rats (6 to 8 weeks old, weighing 200-250 g) were randomly assigned to three groups of 24 rats each: sham, saline and glycyrrhizin. Rats were injected intravenously with lipopolysaccharide (LPS) 24 h after 70% hepatectomy. Glycyrrhizin, pre-administered three times with 24 h intervals 48 h before hepatectomy, prolonged the survival of rats submitted to partial hepatectomy and LPS injection, compared with saline controls. Glycyrrhizin was shown to attenuate histological hepatic changes and significantly reduced serum levels of aspartate aminotransferase, alanine aminotransferase, and lactic dehydrogenase, at all the indicated times (6 rats from each were sacrificed 1, 3, 6, and 9 h after LPS injection), compared with saline controls. Glycyrrhizin also significantly inhibited hepatocyte apoptosis by down-regulating the expression of caspase-3 and inhibiting the release of cytochrome C from mitochondria into the cytoplasm. The anti-inflammatory activity of glycyrrhizin may rely on the inhibition of release of tumor necrosis factor-a, myeloperoxidase activity, and translocation of nuclear factor-kappa B into the nuclei. Glycyrrhizin also up-regulated the expression of proliferating cell nuclear antigen, implying that it might be able to promote regeneration of livers harmed by LPS. In summary, glycyrrhizin may represent a potent drug protecting the liver against endotoxin-induced injury, especially after massive hepatectomy.